EFL Learners’ Perceptions towards their Self-Efficacy in Learning Public Speaking Course - Ima Siti Maryam; R Bunga Febriani; Asep Dudi Kurnia (Universitas Bengkulu, 2019)
This article reports on EFL learners’ perception towards their self-efficacy in public speaking course. Self-ef?cacy has been de?ned as a person’s perceptions of his or her capabilities to complete a speci?c task with the skills that s/he possesses (Bandura, 1997). Thus, It is important for students to measure their skill in order to improve achievement in public speaking course. This research employed a survey study by means of two data collection techniques; questionnaire and interview. The sample of this research was 60 third year students of English department Galuh University. The research result showed that students’ self-efficacy improved after learning public speaking course and the students felt confident using English in front of people. Furthermore, self-efficacy affected not only in public speaking course but also in the other courses. Meanwhile, the high and low self-efficacy might be affected students’ achievements, however, they have similar purpose in public speaking courses, which they want to speak formally without feeling nervous. They have various efforts and strategies to achieve success in this course. This research concludes that self-efficacy in public speaking learning process to third year students of English department Galuh University was important to improve their achievement in speaking skill and improve their confident.